Focus of attention for diagnostic testing of the force-velocity curve. - Brady, C.; Comyns, T.; Harrison, A.; Warrington, G. (Strength and Conditioning Journal, 2017)
Diagnostic testing of various points on the force-velocity curve, such as maximum strength and running speed tests, is used to identify athletes' strengths and weaknesses. During the implementation of these tests, coaches typically use verbal instructions in an attempt to ensure the athlete achieves the highest result possible. Researchers have shown that optimal motor skill performance is often achieved when verbal instructions direct attention externally. This article reviews the current research on the appropriate attentional focus for tests, which assess aspects of the force-velocity curve. Based on an analysis of the existing scientific literature, practical applications are provided for coaches.